Does the KNDy Model for the Control of Gonadotropin-Releasing Hormone Pulses Apply to Monkeys and Humans? - Lehman, Michael N.; He, Wen; Coolen, Lique M.; Levine, Jon E.; Goodman, Robert L. (Seminars in Reproductive Medicine, 2019)
There is now considerable evidence supporting the role of a subpopulation of neurons in the arcuate nucleus of the hypothalamus that coexpress kisspeptin, neurokinin B, and dynorphin (abbreviated as KNDy neurons) as the long sought-after gonadotropin-releasing hormone (GnRH) pulse generator. The “KNDy hypothesis” of pulse generation has largely been based on findings in rodents and ruminants, and there is considerably less information about the anatomical and functional organization of the KNDy subpopulation in the primate hypothalamus. In this review, we focus on the applicability of this hypothesis, and the roles of kisspeptin, neurokinin B, and dynorphin in reproduction, to humans and nonhuman primates, reviewing available data and pointing out important gaps in our current knowledge. With recent application of drugs that target KNDy peptides and their receptors to therapeutic treatments for reproductive disorders, it is imperative we fully understand the primate KNDy network and its role in the control of GnRH secretion, as well as species differences in this system that may exist between humans, nonhuman primates, and other mammals.
Keywords: Kisspeptin; neurokinin B; dynorphin; gonadotropins; estradiol